Pfaffia glomerata is a hyperaccumulator candidate: Cd and Zn tolerance, absorption, transfer, and distribution - Huang, Rong; Wu, Zhimin; Zhao, Xinlin; Li, Feng; Wang, Weidong; Guo, Yuan; Li, Zhian; Wu, Jingtao (Ecotoxicology and environmental safety, 2022)
Pfaffia glomerata is a candidate for phytoremediation due to its high biomass and high bioaccumulation efficiency of multiple heavy metals. It is essential to further evaluate its tolerance, absorption, transfer, and distribution to multiple heavy metals. In the current study, we evaluated the tolerance, absorption, transfer, and distribution of P. glomerata in a Cd/Pb/Cu/Zn combined-contaminated environment by two hydroponic experiments. The results demonstrated that P. glomerata was not affected by Cd/Pb/Cu/Zn exposure, except for the 50 μM Cd/Pb/Cu/Zn treatment, which significantly decreased the stem biomass. In a single Cd, Pb, Cu, and Zn exposure, the root of P. glomerata absorbed Cd/Pb/Cu/Zn in the order of Cd > Zn > Pb > Cu. Almost all Pb and Cu accumulated in the plant roots and were hardly transferred to the aboveground parts. Therefore, the order of total Cd/Pb/Cu/Zn extraction of a single plant in multiple Cd/Pb/Cu/Zn exposures at the same concentration was Cd > Zn > Pb > Cu. The bioconcentration factor (BCF) of Cd and Zn in roots, stems, and leaves increased with the concentration of Cd and Zn in the solution, and was > 1. In contrast with Cd and Zn, the BCFs of Cu and Pb in the stems and leaves were < 1. The element distribution of Pb, Cu, Zn, and Mn in the stem of P. glomerata was dispersed, indicating that the stem of P. glomerata does not have a detoxification mechanism for distributing metals to the area of low biological activity. The total amount of tartaric acid, critic acid, and DOC secreted by P. glomerata roots decreased with the increase in Cd/Pb/Cu/Zn exposure. However, further investigation is needed to unravel the interaction between the LMWOAs secreted by the root of P. glomerata and heavy metals. •The biomass of P. glomerata did not affect by the 10 μM or 30 μM Cd/Pb/Cu/Zn exposure.•The order of total Cd/Pb/Cu/Zn extraction of a single plant was Cd > Zn > Pb > Cu.•P. glomerata does not have a detoxification mechanism for distributing metals to the area of low biological activity.•Cd/Pb/Cu/Zn exposure decreased the secretion of oxalic, tartaric, citric acid, and DOC in the root.